Peningkatan Hasil Belajar Komposisi Fungsi Melalui Penguatan Keterampilan Perkalian dan Operasi Aljabar Sederhana - Wardani, Intan; Hidayah, Shofia; Lesmana, Moh. Fajar Rendra (Papanda, 2025)
This study aims to improve students’ learning outcomes in the topic of function composition through strengthening basic multiplication and simple algebra skills using the Think Pair Share (TPS) learning model. The research was conducted at MAN 1 Probolinggo with 26 students of class XI-A iasisubjects, iselected iusing ipurposive isampling ibased ion ipleliminary ishowing ilow ibasic ialgebra iability iand ilearning iactiveness. iThis study employed a Classroom Action Research (CAR) design following the Kemmis and McTaggart model, which consists of four stages: planning, action, observation, and reflection. Cycle I was carried out in two meetings focusing on reinforcing basic multiplication skills using the jarimatika method and simple algebra exercises, while Cycle was conducted in one meeting emphasizing collaborative activities and a posttest. Data were collected through observations of learning activities and achievement tests. The results showed a significant improvement in students’ learning outcomes, with the average score increasing from 51.15 in the pretest to 68.73 in Cycle I and further to 81.54 in Cycle Students’ learning activities developed from the “fairly active” to the “very active” category. Thus, the integration of the jarimatika method and algebra exercises supported by the TPS model is effective in improving students’ learning outcomes and engagement in mathematics learning